2007
DOI: 10.1007/s00586-007-0374-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between proinflammatory mediator levels in disc material and myelopathy with cervical disc herniation and spondylosis? A non-randomized, prospective clinical study

Abstract: The proinflammatory mediator (PIM) levels were assessed in surgically removed samples of herniated cervical intervertebral discs. The objective of this study was to investigate if there is a correlation between the levels of PIMs in disc material and myelopathy associated with cervical intervertebral disc herniation and spondylosis. The role of proinflammatory mediators in the degeneration of intervertebral disc and the inflammatory effects of disc herniations on radicular pain has been previously published. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Numerous studies report overexpression of TNF-α, IL-1α, and/or IL-1β, IFN-g and IL-6 in patients with protruded, extruded, or sequestered intervertebral disc tissues (14,15,(47)(48)(49)(50). Animal studies also confirm the role of these cytokines in mediating pain (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies report overexpression of TNF-α, IL-1α, and/or IL-1β, IFN-g and IL-6 in patients with protruded, extruded, or sequestered intervertebral disc tissues (14,15,(47)(48)(49)(50). Animal studies also confirm the role of these cytokines in mediating pain (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 92%
“…This study investigated the involvement of inflammatory mediators through the study of lumbar degenerative, herniated, and cadaveric nondegenerated IVD tissues. Prior studies have contributed to understanding of inflammatory processes in pathologic IVD, demonstrating elevated production of prostaglandins, leukotrienes, and thromboxane in herniated disc tissues (11, 20–22). Numerous studies also have revealed either higher expression or simply the presence of the proinflammatory cytokines TNFα, IL‐1α, and/or IL‐1β, IFNγ, and IL‐6 in protruded, extruded, or sequestered disc tissues (3, 4, 12, 20, 21, 23–25).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα is spontaneously produced by IVD tissues ex vivo [5,6], is expressed at higher levels in herniated IVD tissues from symptomatic patients compared to asymptomatic or autoptic controls, and its expression levels increase with increasing radiographic grade of degeneration in the IVD[1,7,8]. Macrophages are key producers of TNFα and their increased presence in herniated and degenerated IVD tissues has been suggested as one of several sources in the IVD[912]. …”
Section: Introductionmentioning
confidence: 99%